DETERMINAN KEPUASAN KERJA KARYAWAN PT RAILINK YOGYAKARTA DENGAN KINERJA SEBAGAI VARIABEL MEDIATOR - Nadia Catherine; Raden Teja Yokanan (Jurnal Riset Manajemen dan Bisnis, 2024)
ABSTRACT The purpose of this research is to examine the effects of perceived organizational support, development, self-efficacy on Job Satisfaction through performance. with sampling done using the Total sampling technique. The sample size for this research was 102 respondents. Data analysis was performed using SmartPLS version 4.0. Based on the findings of the research, providing direct evidence that Perceived Organizational Support and Employee Development has a positive influence on Job Satisfaction. while self-efficacy does not affect Job Satisfaction. Perceived Organizational Support also has a positive impact on Employee Performance, whereas Employee Development does not affect Employee Performance. On the other hand, self-efficacy positively influences Employee Performance, but Employee Performance does not affect Job Satisfaction. Furthermore, Perceived Organizational Support does not directly affect Job Satisfaction through Employee Performance, and Employee Development does not directly affect Job Satisfaction through Employee Performance. Lastly, self-efficacy does not directly affect Job Satisfaction through Employee Performance. Keywords: Perceived Organizational Support, Development, Self-efficacy, Job Satisfaction, Performance ABSTRAK Penelitian ini bertujuan untuk mengetahui apakah pengaruh Perceived Organizational Support, Development, Self-efficacy terhadap Job Satisfaction melalui Performance. Pengambilan sampel menggunakan teknik total sampling. Sampel yang digunakan dalam penelitian ini sebanyak 102 responden. Teknik analisis data menggunakan SmartPLS versi 4.0. Berdasarkan hasil penelitian telah bahwa, Perceived Organizational Support dan Employee Development berpengaruh positif terhadap Job Satisfaction, self-efficacy tidak berpengaruh terhadap Job Satisfaction, Perceived Organizational Support berpengaruh positif terhadap Employee Performance, Employee Development tidak berpengaruh terhadap Employee Performance, self-efficacy berpengaruh positif Employee Performance, Employee Performance tidak berpengaruh terhadap Job Satisfaction, Perceived Organizational Support tidak berpengaruh terhadap Job Satisfaction melalui Employee Performance, Employee Development tidak berpengaruh terhadap Job Satisfaction melalui Employee Performance, self-efficacy tidak berpengaruh terhadap Job Satisfaction melalui Employee Performance. Kata Kunci: dukungan organisasi, pengembangan, efikasi diri, kepuasan kerja, kinerja